1997
DOI: 10.1046/j.1469-1809.1997.6130263.x
|View full text |Cite
|
Sign up to set email alerts
|

Extension of the Haseman–Elston method to multiple alleles and multiple loci: theory and practice for candidate genes

Abstract: The Haseman & Elston (1972) sibling-pair regression method has been used to detect and estimate the variance contribution to observed values of a quantitative trait by allelic variation in specific candidate genes. The procedure was developed under a model with a single biallelic trait locus. This assumption does not hold for several known systems. In this paper we prove that for candidate gene analysis the Haseman-Elston procedure extends to the case of multiple trait loci, each possibly having more t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Looking at all possible pairs of marker loci in the genome and evaluating the significance level of each pair may not be the answer because of the high number of tests required (Dupuis et al 1995), although, for a small number of candidate marker loci, this method does seem to have merit (Cordell et al 1995). Conditional approaches, in which a new locus is searched for, given good evidence for an existing locus or set of loci, appear more promising (Dupuis et al 1995;Cordell et al 2000).In addition to a small number of multilocus approaches (Stoesz et al 1997;Blangero et al 2000), an intriguing method has recently been proposed to allow for the joint analysis of multiple marker loci (Nelson et al 2001). This combinatorial partitioning method (CPM) works by evaluating all possible partitions of marker loci and retaining only those partitions fulfilling certain optimality criteria.…”
mentioning
confidence: 99%
“…Looking at all possible pairs of marker loci in the genome and evaluating the significance level of each pair may not be the answer because of the high number of tests required (Dupuis et al 1995), although, for a small number of candidate marker loci, this method does seem to have merit (Cordell et al 1995). Conditional approaches, in which a new locus is searched for, given good evidence for an existing locus or set of loci, appear more promising (Dupuis et al 1995;Cordell et al 2000).In addition to a small number of multilocus approaches (Stoesz et al 1997;Blangero et al 2000), an intriguing method has recently been proposed to allow for the joint analysis of multiple marker loci (Nelson et al 2001). This combinatorial partitioning method (CPM) works by evaluating all possible partitions of marker loci and retaining only those partitions fulfilling certain optimality criteria.…”
mentioning
confidence: 99%
“…It is not possible within the regression analysis to make inferences about a residual polygenic component because it is confounded with the individual-specific residual error. However, an ad hoc method to account for a residual polygenic effect when estimating the variance contribution by a candidate gene has been proposed by Stoesz et al [1997]. In light of these limitations it is thus interesting, and perhaps surprising, that the HE method detected the APOE gene.…”
Section: Discussionmentioning
confidence: 99%
“…The original presentation of the HE procedure assumed g to be biallelic, but this assumption may be relaxed to higher degrees of polymorphism [Stoesz et al, 1997]. Letting Û 2 g denote the additive component of the genetic variance at g, and Û 2 ‰ the variance of the difference of the residual error between two siblings (e 1 -e 2 ), Haseman and Elston [1972] showed that…”
Section: He Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Assume that the trait X follows the model X = µ + g + e, where µ is an overall mean, g is the effect of a candidate locus which may have multiple alleles (Stoesz et al 1997), and e represents a normally distributed residual with zero mean and variance σ 2 . Let x 1 and x 2 denote the trait phenotypes of two siblings and y = (x 1 −x 2 ) 2 .…”
Section: Methodsmentioning
confidence: 99%